Neck circumference as a complementary measure for identifying excess body weight in children aged from 2 to 9 years - Daniela dos Santos; Silmara Salete de Barros Silva Mastroeni; Cecilia Burigo Corrê; Marco Fabio Mastroeni (Fisioterapia e Pesquisa)
ABSTRACT Neck circumference (NC) indicates nutritional status and indirectly measures upper body subcutaneous fat, an independent predictor of cardiometabolic diseases. This study aims to analyze the accuracy of NC as a measure to assess excess body weight in children aged from two to nine years according to sex. Sampling included 435 children from the Predictors of Maternal and Infant Excess Body Weight Study, a birth cohort study carried out in Brazil in participants’ homes. Data were collected from January 2012 to October 2021. Participants were subjected to anthropometric assessments. Their demographic and socioeconomic data were obtained. A positive correlation (p<0.05) occurred between NC and weight, height, and body mass index in boys and girls in follow-ups. Except for the one-two-year age group (AUC=0.73; 95%CI 0.65–0.81 for boys and girls), the accuracy of NC in indicating excess body weight in boys and girls equaled 0.80 or higher (AUC: 0.80–0.95; 95%CI: 0.71–1.00). Our findings showed that NC can screen Brazilian children aged two-nine years for excess body weight. However, further studies involving larger sample sizes and other populations are necessary to complement the data in this study.